2003
DOI: 10.1080/1071576021000041023
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Cycle Impairment Mediates Aβ-induced Cell Toxicity

Abstract: Alzheimer's disease is widely held to be associated with oxidative stress due, in part, to the action of amyloid beta-peptide (A beta). We observed that A beta 25-35 induced an increase in reactive oxygen species (ROS) in NT2 rho+ cells, leading to protein and lipid oxidation. This oxidative status was partially prevented by the antioxidants, vitamin E, reduced glutathione, and by melatonin. However, NT2 rho0 cells (that lack mitochondrial DNA) in the absence of A beta showed an increase in ROS production, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Astrocytes provide reduced glutathione, the principal cellular antioxidant (Peuchen et al, 1997;Dringen, 2000). Notably, glutathione cycle impairment has been described after 25-35 A␤ peptide treatment (Casley et al, 2002;Cardoso and Oliveira, 2003). This observation could explain why we noticed a decrease of astrocytic protection after A␤ treatment.…”
Section: Discussionmentioning
confidence: 41%
“…Astrocytes provide reduced glutathione, the principal cellular antioxidant (Peuchen et al, 1997;Dringen, 2000). Notably, glutathione cycle impairment has been described after 25-35 A␤ peptide treatment (Casley et al, 2002;Cardoso and Oliveira, 2003). This observation could explain why we noticed a decrease of astrocytic protection after A␤ treatment.…”
Section: Discussionmentioning
confidence: 41%
“…Others reported that the effect of Zn 2+ on preventing caspase-3 activation and apoptotic cell death could be due to the regulation of cellular redox potential involving GSH (Nakatani et al, 2000). This action of Zn 2+ on the glutathione cycle could be relevant, since Aβ 25-35 induces the decrease of the cellular GSH (Cardoso et al, 2003).…”
Section: +mentioning
confidence: 95%
“…As previously discussed, the reduction in GSH levels is in accordance with earlier reports from studies with AD brain 28 and also with other in vitro studies. 29 The decrease in GSH levels could further suggest that glutathione participates in the recuperation of reduced GRX1 seen at 24 h (see Figure 1). On the other hand, the recuperation of reduced TRX1, seen at 24 h, could indicate an additional upregulation of the reducing Several reports have shown that Ab induces apoptosis in a number of different models (for a review, see Small et al…”
Section: Discussionmentioning
confidence: 99%
“…Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and Ab were purchased from Sigma-Aldrich (Stockholm, Sweden). Ab(1-42) was from US Peptide (Rancho Cucamonga, CA, USA) and dissolved in serum-free minimum essential medium (MEM).…”
Section: Methodsmentioning
confidence: 99%